Una vita violenta - Piccioni, Piero 1921-2004 (Minerva Classic, 2006)
Set in post-war Italy, the film chronicles the deeds of young Tommaso, a reckless hoodlum who spends his time on the streets of Rome. Flirting with both the Fascists and the Communists, Tommaso unexpectedly falls in love with the beautiful Irene. A brawl lands him in jail, where he contracts tuberculosis. He develops a social conscience after a stay in a sanitarium and rescues a prostitute from drowning